2022
DOI: 10.1186/s12711-022-00706-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the choice of animals for re-sequencing in two maternal pig lines

Abstract: Next-generation sequencing is a promising approach for the detection of causal variants within previously identified quantitative trait loci. Because of the costs of re-sequencing experiments, this application is currently mainly restricted to subsets of animals from already genotyped populations. Imputation from a lower to a higher marker density could represent a useful complementary approach. An analysis of the literature shows that several strategies are available to select animals for re-sequencing. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
(55 reference statements)
1
4
0
Order By: Relevance
“…In the previous study, it was noted that there has been limited application of systematic studies utilizing the mentioned methods in chicken populations. However, consistent with prior investigations on pigs ( Dauben et al, 2022 ), based on practical data, and cattle ( Druet et al, 2014 ), based on simulated data, targeted selection techniques exhibit superior imputation performance compared to random selection. Additionally, Dauben et al reported that combining samples derived from pedigree-based and haplotype-based methodologies resulted in higher imputation accuracy than using haplotype-based samples alone, a finding that is congruent with our current study.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…In the previous study, it was noted that there has been limited application of systematic studies utilizing the mentioned methods in chicken populations. However, consistent with prior investigations on pigs ( Dauben et al, 2022 ), based on practical data, and cattle ( Druet et al, 2014 ), based on simulated data, targeted selection techniques exhibit superior imputation performance compared to random selection. Additionally, Dauben et al reported that combining samples derived from pedigree-based and haplotype-based methodologies resulted in higher imputation accuracy than using haplotype-based samples alone, a finding that is congruent with our current study.…”
Section: Discussionsupporting
confidence: 71%
“…To identify the reference broilers, 4 distinct strategies were evaluated, as outlined in the study by Dauben et al (2022) . These approaches are designated by the letters H, P, C, and R, which respectively stand for haplotype-based, pedigree-based, combined, and random sampling.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations